1984
DOI: 10.1104/pp.74.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Host Recognition in the Rhizobium-Soybean Symbiosis

Abstract: The mechanism of host-symbiont recognition in the soybean-Rhizobium symbiosis was investipted utilizing mutants of R. japonicum defective in nodulation. Soybeans were grown in clear plastic growth pouches allowing the identifcation of the area on the root most susceptible to Rhizobium nodulation; the area between the root tip (RT) and smallest emergent root hair (SERH). The location of nodules in relation to this developing zone is an indication of the rate of nodule initiation. Nodules were scored as to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…It appears that the nodE mutant strain of R. leguminosarum may be unable to capitalize on the initial period of infectibility but could subsequently induce infection, thus showing a delayed nodulation phenotype. A mutant of R. japonicum with a similar phenotype has been described previously (10), and it was shown that with this strain the delayed initiation of nodulation could be reversed by the addition of root exudate from soybean seedlings. Interestingly, it appears that the phenotype of the nodE mutant strain described here could be at least partially reversed if the seedlings were grown initially in the absence of light.…”
Section: Resultsmentioning
confidence: 99%
“…It appears that the nodE mutant strain of R. leguminosarum may be unable to capitalize on the initial period of infectibility but could subsequently induce infection, thus showing a delayed nodulation phenotype. A mutant of R. japonicum with a similar phenotype has been described previously (10), and it was shown that with this strain the delayed initiation of nodulation could be reversed by the addition of root exudate from soybean seedlings. Interestingly, it appears that the phenotype of the nodE mutant strain described here could be at least partially reversed if the seedlings were grown initially in the absence of light.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, observations were restricted to the region of the root containing cells competent to be infected, i.e. the zone of no and emerging root hairs (4,6,19 (2,3,14). The effect of these solutions on nodulation is thought to reflect changes in the behavior of rhizobia before infection, and thus it was of interest to determine if culture of rhizobia in similar solutions enhanced bacterial adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…For delayed-nodulation assays and comparison of nodulation ability on different soybean cultivars (i.e., Glycine max cv. Essex, Harosoy, Williams, Forest, and Peking), seedlings were sprouted as before and then grown three to a pack in clear plastic pouches (Dispo Seed Pack; Northrup King Seed Co.) as described previously (24).…”
Section: Methodsmentioning
confidence: 99%